Fungal Unspecific Peroxygenases Oxidize the Majority of Organic EPA Priority Pollutants - Karich, Alexander; Ullrich, René; Scheibner, Katrin; Hofrichter, Martin (Frontiers in Microbiology, 2017)
Unspecific peroxygenases (UPOs) are secreted fungal enzymes with promiscuity for oxygen transfer and oxidation reactions. Functionally, they represent hybrids of P450 monooxygenases and heme peroxidases; phylogenetically they belong to the family of heme-thiolate peroxidases. Two UPOs from the basidiomycetous fungi Agrocybe aegerita (AaeUPO) and Marasmius rotula (MroUPO) converted 35 out of 40 compounds listed as EPA priority pollutants, including chlorinated benzenes and their derivatives, halogenated biphenyl ethers, nitroaromatic compounds, polycyclic aromatic hydrocarbons (PAHs) and phthalic acid derivatives. These oxygenations and oxidations resulted in diverse products and – if at all – were limited for three reasons: (i) steric hindrance caused by multiple substitutions or bulkiness of the compound as such (e.g. hexachlorobenzene or large PAHs), (ii) strong inactivation of aromatic rings (e.g. nitrobenzene) and (iii) low water solubility (e.g. complex arenes). The general outcome of our study is that UPOs can be considered as extracellular counterparts of intracellular monooxygenases, both with respect to catalyzed reactions and catalytic versatility. Therefore, they should be taken into consideration as a relevant biocatalytic detoxification and biodegradation tool used by fungi when confronted with toxins, xenobiotics and pollutants in their natural environments.